Sistem Pengendalian Internal Pengeluaran Kas pada PT. Telkom Indonesia (Persero) Tbk. Witel SULBANGSEL - Dwiyanti, Rizky; Ramlah, St (Tangible Journal, 2025)
The purpose of this study is to analyze the internal control system for cash disbursements at PT. Telkom Indonesia (Persero) Tbk Witel SULBAGSEL 2024. The type of research used is descriptive qualitative with data collection techniques in the form of interviews, documentation, and observation and using data analysis methods based on the COSO (Committee of Sponsoring Organizations of the Treadway Commission) control components. The results of the study indicate that, PT. Telkom Indonesia (Persero) Tbk Witel SULBAGSEL has implemented the Internal Control System for Cash disbursement well, only the Standard Operating Procedure (SOP) used is still the old one that does not exist regarding the system used for the cash disbursement process because it has not submitted a request to the central office.